2016
DOI: 10.3892/etm.2016.3763
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cytomegalovirus infection on the prognosis of inflammatory bowel disease patients

Abstract: The aim of the present study was to investigate the effects of cytomegalovirus (CMV) infection on the prognosis of inflammatory bowel disease (IBD). Various databases were searched using a combination of keywords associated with CMV infection and IBD. Subsequent to the selection of relevant studies in line with strict inclusion and exclusion criteria, a meta-analysis was conducted using the Stata 12.0 software. A total of 195 studies were initially retrieved, including 28 studies in Chinese and 167 in English.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…26 A recent meta-analysis revealed that cytomegalovirus [CMV] infection in IBD may be associated with longer disease duration, reduced efficacy of corticosteroid therapy, and increased colectomy rate. 222 Corticosteroid and thiopurine exposure are associated with reactivation of latent CMV. 223 However, tissue damage following exposure to immunomodulators is rare.…”
Section: Monitoring Clinically Symptomatic Patientsmentioning
confidence: 99%
“…26 A recent meta-analysis revealed that cytomegalovirus [CMV] infection in IBD may be associated with longer disease duration, reduced efficacy of corticosteroid therapy, and increased colectomy rate. 222 Corticosteroid and thiopurine exposure are associated with reactivation of latent CMV. 223 However, tissue damage following exposure to immunomodulators is rare.…”
Section: Monitoring Clinically Symptomatic Patientsmentioning
confidence: 99%
“…Depending on the clinical setting, PCR for viral and parasitic agents may be considered. For example, IBD patients receiving immunosuppression are more prone to CMV colitis, which can be measured in serum and biopsies [ 25 ]. Blood cultures are mandatory.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies presume that CMV infections may have a significant role in the outcome of patients with inflammatory bowel diseases, especially if the patients undergo immunosuppressive treatment. Higher morbidity rates were observed in patients with present CMV infection and ulcerative colitis or Crohn's disease [12]. The European Crohn's and Colitis Organisation states in its recent guidelines that acute CMV infection due to reactivation of the virus under immunosuppression is common, but severe courses are rather rare.…”
Section: Discussionmentioning
confidence: 99%